A cross cultural examination of the concentration skills of elite level athletes - Nideffer, R. M.; Bond, J.
Distractibility scores for male athletes suggest that the pattern of their concentration errors is fairly consistent. More often than not, their mistakes occur because they think too much, become distracted by their own thoughts. Females on the other hand, are just as likely to become distracted by external events (e.g., what their opponent is doing), as they are by their own thoughts. Basic training for males should include learning how to shut off some of their analytical thought processes. As pressure increases, many males need to learn to let go of their own thoughts and to redirect their focus to the events going on around them. They need to pay more attention to their opponent. Females, because of their increased sensitivity and reactivity to, environmental cues need to learn to let go of the external distractions, to find appropriate times to shut them out so they can more effectively problem solve. Both male and female athletes share a highly competitive nature. Their competitiveness combined with their need to be in control causes them to become angry when they make mistakes and/or when things aren't going the way they planned or hoped they would. Because of the attentional differences, that anger often gets directed in different ways. Females have a greater tendency to become angry with and/or irritated by opponents. Males, tend to focus the anger internally. They become angry with themselves. In either case, unless the anger is kept within reasonable bounds, performance deteriorates. Both males and females need to learn to "take the top off their anger." By that I mean they need to be able to reduce to the point that the arousal can help them focus, but not be so high as to interfere with their ability to make appropriate shifts from an external to an internal focus and vice versa. Females need to be able to shift internally, and use the anger and the focus associated with it, to help the problem solve. Males need to learn to use the anger to help them focus on the external environment.